Optimized Transformation and Gene Editing of the B104 Public Maize Inbred by Improved Tissue Culture and Use of Morphogenic Regulators - Aesaert, Stijn; Impens, Lennert; Coussens, Griet; Van Lerberge, Els; Vanderhaeghen, Rudy; Desmet, Laurence; Vanhevel, Yasmine; Bossuyt, Shari; Wambua, Angeline Ndele; Van Lijsebettens, Mieke; Inzé, Dirk; De Keyser, Ellen; et al. (Frontiers in Plant Science, 2022)
Plant transformation is a bottleneck for the application of gene editing in plants. In Zea mays (maize), a breakthrough was made using co-transformation of the morphogenic transcription factors BABY BOOM (BBM) and WUSCHEL (WUS) to induce somatic embryogenesis. Together with adapted tissue culture media this was shown to increase transformation efficiency significantly. However, use of the method has not been reported widely, despite a clear need for increased transformation capacity in academic settings. Here, we explore use of the method for the public maize inbred B104 that is widely used for transformation by the research community. We find that only modifying tissue culture already boosts transformation efficiency significantly and can reduce the time in tissue culture by one month. On average, production of independent transgenic plants per starting embryo increased from 1 to 4% using BIALAPHOS RESISTANCE as a selection marker. In addition, we reconstructed the BBM-WUS morphogenic gene cassette and evaluated its functionality in B104. Expression of the morphogenic genes under tissue- and development stage-specific promoters led to direct somatic embryo formation on the scutellum of zygotic embryos. However, eight out of ten resulting transgenic plants showed pleiotropic developmental defects and were not fertile. This undesirable phenotype was positively correlated with the copy number of the morphogenic transgenes. Use of constructs in which morphogenic genes are flanked by a developmentally controlled Cre/LoxP recombination system led to reduced T-DNA copy number and fertile T0 plants, while increasing transformation efficiency from 1 to 5% using HIGHLY-RESISTANT ACETOLACTASE SYNTHASE as a selection marker. Addition of a CRISPR/Cas9 module confirmed functionality for gene editing applications, as exemplified by the editing the gene VIRESCENT YELLOW-LIKE that can act as a visual marker for gene editing in maize. The constructs, methods and insights produced in this work will be valuable to translate the use of BBM-WUS and other emerging morphogenic regulators to other genotypes and crops.